Tjina ydubry gap pom mo (Nosso território com morro grande): histórias, memória coletiva e percepções sobre o território e a biodiversidade entre os Arara (Karib) da TI Cachoeira Seca - BUILES PUERTAS, Diego Fernando (Universidade Federal do Pará, 2025)
The Arara (Karib) indigenous people of Pará, were particularly famous in the 1980s, when news became widespread from local media to national and international spheres, about conflicts between, Arara people groups with settlers and non-indigenous workers who arrived following the colonization and development initiatives of the military government in the 1960s. To continue the works and projects, the government created the Arara Attraction Front (AAF) since 1971. In 1982 and 1983, a AAF was contact the Arara groups that make up the current “Arara Indigenous Land”, and in 1987, was contact the last Arara group that inhabiting a current “Cachoeira Seca Indigenous Land”. Even though the limits of the Cachoeira Seca Indigenous Land were approved in 2016, the regularization was not completed, due to the setbacks in the process, and non-indigenous people, remain in the Indigenous Land. Taking advantage of loopholes in the process, illegal invaders deforest, traffic in timber, grab land, raise livestock, and exploit resources for exclusive use, ignoring constitutional and legal provisions. Another structural issue, consisting of the legitimization of asymmetrical actions of invasion and seizure of the territory of indigenous peoples, based on the rhetorical discourses of “empty territory” or inhabited by “people lacking useful knowledge for civilization”, has also taken effect, in imposition of economic and political interests. Due to the interaction of all these elements, and their continuity, despite permanent community complaints and the actions of institutions in charge of protecting the territory and biodiversity, the situation is framed as a problem of lack of efficiency and effectiveness in policies and actions of territorial protection of the Cachoeira Seca Indigenous Land. To contribute to improving this situation, we analyzed the forms of use of the territory and biodiversity, based on documentary information, the record of collective memory and the documentation of perceptions and the traditional knowledge collection of the Arara people of Cachoeira Seca Indigenous Land. Documentary review, interaction in the villages and recording in a field diary were used. Participatory and collaborative workshops, mapping and zoning, conversations, interviews and monitoring expeditions to areas of biodiversity use were also held. In chapter I, the historical elements analyzed are presented, focusing on the Arara (Karib) people and their traditional territory in Xingu Region. In chapter II, elements of the diaspora and mobility of the Arara groups are presented in dialogue with the collective memory of Tjibie Arara and her daughter Iogo Arara about of contact experience with the karei (non-indigenous people). In chapter III, elements on perceptions and the traditional knowledge about the territory and biodiversity use, for food and survival are presented. Maps and figures are presented with reconstructions of historical mobility; details of the fragmentation of the Arara groups territory by colonization and development projects; cultural and food calendars; and the ethno zoning of Special Indigenous Management Areas (AMEIs in Portuguese language) and Territorial Areas of Recurrent Invasions after the “Transamazonic highway” construction (ATRITs in Portuguese language).